The online educated or online indoctrinated human? Discourse analysis as a method to study ideologies disseminated by online courses - Platonova, Iuliia (HTS teologiese studies, 2019)
Online courses attract thousands, even millions of students from all corners of the Earth. As such, they have the potential to educate many people. Education, however, is not neutral. Knowledge is embedded in contexts and perspectives, carrying ideological baggage, and so is teaching and learning. Teaching can no longer be the mere provision of content. The knowledge explosion implies that the ability to master content should become part and parcel of the course curriculum. In the same vein, the fact that online courses attract students from many different contexts necessitates that lecturer and student alike should be aware of the underlying ideologies in the course content. To this end, in this conceptual article it is argued that discourse analysis of not only the written course content but also of images used to illustrate the content can be helpful; these are often not scrutinised for ideological baggage. If not, the online educated human might become the online indoctrinated human, to the detriment of all.